The right to vote and the law relating to election petitions, 26th, February 2000 - De Alwis, Sundari; Vikalpa Pratipatti Kēndraya (Colombo, Sri Lanka) (Colombo : Centre for Policy Alternatives, 2000)
Contributed articles presented at a seminar with reference to Sri Lanka.
Keywords: Election law -- Sri Lanka